2021
DOI: 10.7202/1077724ar
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Applications to Support Indigenous Youth Wellbeing in Canada

Abstract: In Canada, Indigenous youth have remained resilient despite being confronted with a wide range of structural and systemic risks, such as long-lasting boil water advisories, over-representation in the child welfare system, and injustices related to land treaties. As people of the land, all disruptions to ecological health are a disruption to personal and community holistic health. Land-based activities and cultural continuity strengthen pathways of perseverance for Indigenous youth (Toombs et al., 2016). For yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For Haudenosaunee, mental health is embedded in their notion of Ganikwi: yo or good mind established in the Great Law of Peace. A good mind is achieved through living in peace, balance, and harmony with all creation (Noronha et al, 2021). Noronha et al (2021) adapted the Haudenosaunee wellness model collected from the Kawenni:io/Gaweni:yo private school to demonstrate that for Haudenosaunee, both good mental health and resilience depend on a good mind, family, community, environment, and spirituality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For Haudenosaunee, mental health is embedded in their notion of Ganikwi: yo or good mind established in the Great Law of Peace. A good mind is achieved through living in peace, balance, and harmony with all creation (Noronha et al, 2021). Noronha et al (2021) adapted the Haudenosaunee wellness model collected from the Kawenni:io/Gaweni:yo private school to demonstrate that for Haudenosaunee, both good mental health and resilience depend on a good mind, family, community, environment, and spirituality.…”
Section: Discussionmentioning
confidence: 99%
“…A good mind is achieved through living in peace, balance, and harmony with all creation (Noronha et al, 2021). Noronha et al (2021) adapted the Haudenosaunee wellness model collected from the Kawenni:io/Gaweni:yo private school to demonstrate that for Haudenosaunee, both good mental health and resilience depend on a good mind, family, community, environment, and spirituality. Further, they demonstrated that mental health issues such as stress, anxiety, and depression are not universal, nor are their healings; instead, they vary in different cultures (Kleinman and Good, 1986;Kelm, 1998;Adelson, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-compassion resonates in various Indigenous cultures. For example, Haudenosaunee perspectives include kindness and gratitude as part of the concept of “good mind, ” which is more communally defined in terms of the power of the mind that is unified amongst relatives than individually-focused ( 81 ). The Mohawk word for compassion translates as “love among us” (A.…”
Section: Supporting Self-compassion and Dampening Fear Of Self-compas...mentioning
confidence: 99%